Phase III In The Development Stages Of Anatolian Alevi’s Settlement In Anatolia (Journal of Alevism-Bektashism Studies, 2010)
This article investigates the multilateral reasons and results of the settlement of the grazier communities into Anatolia. At the same time, it focuses on the sources of the perception of Islam and the resulting structure that emerged after the settlement of the grazier communities. The article tries to prove and document that the understanding brought in from Khorasan is a one systemized in form of a special Hz. Ali and Ahl al-Bayt belief in Anatolia. The author defends that this belief in Anatolia, different from the Islam based understanding of Hz. Ali and the Ahl al-Bayt is in different parts of the world should be more proper to be named as “Anatolian Alevism”